PENGARUH JARAK PERTAMBANGAN EMAS SKALA KECIL (PESK) TERHADAP MERKURI DALAM AIR SUNGAI DAN BENTHOS DI KABUPATEN BANDUNG - Agustina, Risna; -, Nurhayati; Lekatompessy, Benjamin J. (JURNAL TECHLINK, 2023)
Small Scale Gold Mining (ASGM) in Indonesia is carried out using amalgamation techniques which produce mercury waste and have the potential to pollute the surrounding environment. Mercury contamination is suspected to have occurred in the Ciherang River. This study aims to analyze mercury levels in river water and the benthos of the Ciherang River with a difference of 0.28 km before mining, 0.51 km after mining and 1.42 km after mining. Water and benthos samples were taken using a water sampler while benthos used an Ekman grab which was then taken to the laboratory and analyzed for mercury levels with a mercury analyzer. The mercury level in Ciherang River water ranges from 0.0002 mg/L – 0.0005 mg/L. While the mercury content in benthos ranges from 0.04 mg/kg – 0.2 mg/kg.